2016
DOI: 10.1155/2016/6950154
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-Layer Characteristics of Persistent Regional Haze Events and Heavy Haze Days in Eastern China

Abstract: This paper analyzed the surface conditions and boundary-layer climate of regional haze events and heavy haze in southern Jiangsu Province in China. There are 5 types with the surface conditions which are equalized pressure (EQP), the advancing edge of a cold front (ACF), the base of high pressure (BOH), the backside of high pressure (BAH), the inverted trough of low pressure (INT), and saddle pressure (SAP) with the haze days. At that time, 4 types are divided with the regional haze events and each of which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Previous studies also reported that weather conditions were critical for haze formation. In eastern China, migratory anticyclones and weak pressure gradients were the prerequisites of winter haze from 1980 to 2012 (Peng et al, 2016). High PM 2.5 episodes in Beijing usually began with weak southerly winds and ended with strong northerly winds (Guo et al, 2014).…”
Section: Chemical and Meteorological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also reported that weather conditions were critical for haze formation. In eastern China, migratory anticyclones and weak pressure gradients were the prerequisites of winter haze from 1980 to 2012 (Peng et al, 2016). High PM 2.5 episodes in Beijing usually began with weak southerly winds and ended with strong northerly winds (Guo et al, 2014).…”
Section: Chemical and Meteorological Characteristicsmentioning
confidence: 99%
“…Considering the extreme haze situation in Beijing, researchers have sought the crucial factors of haze formation, usually by identifying the emission sources of PM 2.5 . The source apportionment of PM 2.5 is commonly analyzed by source receptor models such as positive matrix factorization (PMF) and non-negative matrix factorization (NMF; Reff et al, 2007;Kfoury et al, 2016). These models have implicated coal and industries as major sources of PM 2.5 in Beijing (Huang et al, 2014;Zhang and Cao, 2015;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also reported that weather conditions were critical for haze formation. In eastern China, migratory anticyclones and weak pressure gradients were the prerequisites of winter haze from 1980 to 2012 (Peng et al, 2016). High PM 2.5 episodes in Beijing usually began with weak southerly winds and ended with strong northerly winds Figure 3.…”
Section: Chemical and Meteorological Characteristicsmentioning
confidence: 99%
“…A haze episode may be induced by one or a number of factors combined, which encompasses emissions, secondary aerosols [13][14][15][16][17], and atmospheric transport [8,17], with unfavorable weather conditions acting as an accelerating factor [18][19][20][21][22][23][24][25]. The effects of the atmospheric boundary layer (ABL) structure, near-surface atmospheric stability, and synoptic conditions have received the attention given that they strongly dictate how haze and its associated thermal and dynamical processes evolve with time in the lower part of the troposphere [23][24][25]. Quan et al (2013) [19] and Petaja et al (2016) [20] suggested a positive feedback cycle for heavy air pollution where heat flux decrease significantly due to decreased solar radiation blocked by the haze layer, which in turn further decreases ABL height and trap air pollutant within.…”
Section: Introductionmentioning
confidence: 99%
“…Haze pollution has been studied globally to understand its formation and evolution mechanism [ 4 , 5 , 6 , 7 ], potentials sources contribution [ 5 , 8 , 9 ], mitigation strategies [ 10 , 11 ], and early warning or forecasting [ 12 ]. A haze episode may be induced by one or a number of factors combined, which encompasses emissions, secondary aerosols [ 13 , 14 , 15 , 16 , 17 ], and atmospheric transport [ 8 , 17 ], with unfavorable weather conditions acting as an accelerating factor [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The effects of the atmospheric boundary layer (ABL) structure, near-surface atmospheric stability, and synoptic conditions have received the attention given that they strongly dictate how haze and its associated thermal and dynamical processes evolve with time in the lower part of the troposphere [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%